CBMT-11. HIGH MITOCHONDRIAL DNA COPY NUMBER IS ASSOCIATED WITH LONGER SURVIVAL IN YOUNG PATIENTS WITH GLIOBLASTOMA. (11th November 2019) - Rousseau, Audrey; Dardaud, Laure-Marie; Bris, Céline; Desquiret-Dumas, Valérie; Boisselier, Blandine; Tabouret, Emeline; Mokhtari, Karima; Figarella-Branger, Dominique; Procaccio, Vincent
Abstract: Young patients (< 40 years-old) with glioblastoma (GB) may carry IDH1/2 mutations or rarely, H3F3A/HIST1H3B mutations. Some instead harbor chromosome (chr) 7 gain, chr 10 loss, and EGFR amplification (amp). IDH1/2 mutations are associated with longer survival in contrast to H3F3A/HIST1H3B mutations. Novel reliable prognostic factors are needed in GB. Mitochondria (mt) are responsible for ATP production through oxidative phosphorylation. High mtDNA copy number (CN) has been associated with variable outcomes in cancer. The mtDNA-CN was assessed by RT Q-PCR in 66 GB from patients 18 to 40 years-old. Whole mitochondrial genome sequencing was performed in 18/66 GB. 17/66 (25.8%) cases harbored IDH1-R132H mutation; 29/66 (44%) had chr 7 gain/chr 10 loss and/or EGFRamp; 4/66 (6%) harbored H3F3A/HIST1H3B mutations. The remaining cases (24.2%) had no key genetic alterations. The mtDNA/nuclearDNA ratio was subdivided into groups: Low and High according to the median (mtDNA-CN median 194.9). 33 patients displayed a low ratio (≤ median) whereas 33 displayed a high ratio (> median). The overall survival in the High vs Low group was significantly longer in the whole cohort (Log-rank test, 31.8 vs 14.2 months, p= 0.019) and the chr7+/chr10-/EGFRamp subgroup (37.8 vs 12.1 months; p= 0.0117). There was still a trend towards longer survival in the High vs Low group within the other genetic subgroups (IDH-mutant; no genetic alteration) except for the H3-mutant GB (4 patients). Analyses on 232 patients 18 to 84 years-old showed that among patients < 56 years-old, the High group (58 cases) had a longer survival compared to the Low group (59 cases) (27.3 vs 15 months; p= 0.023). High mtDNA level is linked to oxidative metabolism (which decreases tumor aggressiveness) and cell differentiation. Increasing mtDNA-CN might induce tumor cell differentiation and slow disease progression. In conclusion, mtDNA-CN may be a novel prognostic biomarker in GB.